Cholangitis lenta: An underdiagnosed lesion associated with severe cholestasis following liver transplantation. Issue 9 (17th July 2020) - Bonal, Mathieu; Mourad, Mohamed; Bancel, Brigitte; Hervieu, Valérie; Lebossé, Fanny; Heyer, Laurent; Ducerf, Christian; Lesurtel, Mickaël; Mabrut, Jean‐Yves; Mohkam, Kayvan
Abstract: Background: Cholangitis lenta (CL) represents a specific histological lesion associated with severe cholestasis and related to sepsis. Despite being well known by pathologists, CL has been poorly studied in liver transplantation (LT). Methods: We performed a retrospective 12‐year analysis of the incidence, risk factors, and outcome of CL in LT recipients. Biopsy samples performed within 3 months after LT underwent blinded rereading to identify recipients with CL. Results: Among 587 LT performed, 45 (7.7%) developed CL. Of these, 7 (15.6%) had no signs of clinical sepsis at the time of biopsy, but further investigations revealed positive cultures. Independent factors associated with CL were sepsis at the time of LT (OR = 3.62 [95%CI = 1.63‐8.06]), donor age (OR = 1.05 [1.03‐1.08]), and operative time (OR = 1.23 [95%CI = 1.02‐1.48]). Cholangitis lenta was associated with increased severe morbidity (71.1% vs 33.0%, P  < .001), 90‐day mortality (24.4% vs 5.9%, P  < .001) and decreased one‐year graft (62.1% vs 89.4%, P  < .001) and patient survival (55.6% vs 87.9%, P  < .001). Conclusion: Cholangitis lenta represents a possible lesion associated with cholestasis after LT, which strongly affects its outcome. In the event of an unexplained post‐transplant cholestasis, the diagnosis of CL must be considered, even in the absence of clinically evident sepsis.